Intensity and timing of warming and drought differentially affect growth patterns of co-occurring Mediterranean tree species - Granda, Elena; Julio Camarero, J; Gimeno, Teresa E; Martínez-Fernández, Jesús; Valladares, Fernando (EUROPEAN JOURNAL OF FOREST RESEARCH, 2013)
Climate change involves warmer temperatures, altered precipitation patterns, increased climatic variability and, in Mediterranean regions, increased frequency and severity of droughts. Tree species may show different growth responses to these components of climatic change, which may trigger changes in forest composition and dominance. We assessed the influence of recent climatic changes on secondary growth of mature trees from four species co-occurring in a Mediterranean continental forest: Quercus ilex, Quercus faginea, Pinus nigra and Juniperus thurifera. We used dendrochronology to relate radial-growth variables \{[\}earlywood and latewood widths, basal area increment (BAI)] to annual and seasonal climatic variables for the period 1977-2007. Our results showed that Q. faginea BAI has declined, whereas J. thurifera BAI has increased over time while Q. ilex and P. nigra have maintained their growth rates. Growth was mainly favored by higher precipitations and tree size for all species. Reduced growth during extremely dry years was observed for all study species, but all of them except Q. faginea recovered their growth levels 2 years after drought. Our findings illustrate how the effects of climatic changes on growth should include analyses of seasonal climatic trends and extreme events such as severe droughts. We conclude that the seasonal timing of warming and precipitation alterations leading to drought events caused contrasting effects on growth of co-occurring Mediterranean tree species, compromising their future coexistence.
Keywords: climate change; Coexistence; Dendroecology; Drought; Mediterranean forests; Radial growth

The decreased competition in expanding versus mature juniper woodlands is counteracted by adverse climatic effects on growth - Gimeno, Teresa E.; Pías, Beatriz; Martínez-Fernández, Jesús; Quiroga, David L.; Escudero, Adrián; Valladares, Fernando (European Journal of Forest Research, 2011)
World-wide deforestation is being reversed in Mediterranean continental areas, where abandonment of traditional practises favours the expansion of valuable habitats, like Juniperus thurifera woodlands. We hypothesised that pre-existing trees facilitate establishment in expanding woodlands, whereas in mature woodlands, competition leads to patch disaggregation. We compared the imprint of these processes on growth, demographic and spatial structure of expanding and mature J. thurifera woodlands. We selected plots where we geopositioned, aged and quantiﬁed the morphological characteristics of all trees. In the mature woodland, trees arranged in clumps and randomly in the expanding woodland. Competition negatively affected growth, was greater in the mature woodland and led to disaggregation of juvenile clumps. Differences in growth between the mature and the expanding woodland disappeared in climatically unfavourable years, suggesting that adverse climate constrains growth more in expanding than in mature woodlands. We suggest that change in the dispersal agents and a decrease of facilitation underlay differences in spatial patters between the expanding and the mature woodland. Observed effective recruitment in less than 30 years into the expanding woodland evidenced that propagule arrival and sapling survival do not constrain woodland expansion. Furthermore, growth of juveniles established in these new areas is favoured by reduced intraspeciﬁc competition. However, we expect growth in expanding woodlands to be negatively impacted by climate change. We conclude that under current global change scenario, conservation of J. thurifera woodlands is favoured by changes in land use, but greater frequency and severity of drier than usual episodes could hamper natural reforestation.
Keywords: Juniperus thurifera; Plant–plant interactions; Radial growth; Spatial pattern; Woodland expansion; Woodlandisation